Activation of hip prostheses in high energy radiotherapy and resultant dose to nearby tissue. (27th February 2017) - Keehan, Stephanie; Smith, Ryan L.; Millar, Jeremy; Esser, Max; Taylor, Michael L.; Lonski, Peta; Kron, Tomas; Franich, Rick D.
Abstract: High energy radiotherapy can produce contaminant neutrons through the photonuclear effect. Patients receiving external beam radiation therapy to the pelvis may have high‐density hip prostheses. Metallic materials such as those in hip prostheses, often have high cross‐sections for neutron interaction. In this study, Thackray (UK) prosthetic hips have been irradiated by 18 MV radiotherapy beams to evaluate the additional dose to patients from the activation products. Hips were irradiated in‐ and out‐of field at various distances from the beam isocenter to assess activation caused in‐field by photo‐activation, and neutron activation which occurs both in and out‐of‐field. NaI(Tl) scintillator detectors were used to measure the subsequent gamma‐ray emissions and their half‐lives. High sensitivity Mg, Cu, P doped LiF thermoluminescence dosimeter chips (TLD‐100H) were used to measure the subsequent dose at the surface of a prosthesis over the 12 h following an in‐field irradiation of 10, 000 MU to a hip prosthesis located at the beam isocenter in a water phantom. 53 Fe, 56 Mn, and 52 V were identified within the hip following irradiation by radiotherapy beams. The dose measured at the surface of a prosthesis following irradiation in a water phantom was 0.20 mGy over 12 h. The dose at the surface of prostheses irradiated to 200 MU was below the limit of detection (0.05 mGy) of the TLD100H. Prosthetic hips are activated by incident photons and neutrons in high energy radiotherapy, however, the dose resulting from activation is very small.